2014
DOI: 10.1158/1541-7786.mcr-14-0054
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Potential of DNA Methylation and Transcript Levels of HIF1A and EPAS1 in Colorectal Cancer

Abstract: Hypoxic conditions during the formation of colorectal cancer may support the development of more aggressive tumors. Hypoxia-inducible factor (HIF) is a heterodimeric complex, composed of oxygen-induced HIFa and constitutively expressed HIFb subunits, which mediates the primary transcriptional response to hypoxic stress. Among HIFa isoforms, HIF1a (HIF1A) and endothelial PAS domain-containing protein 1 (EPAS1) are able to robustly activate hypoxia-responsive gene signatures. Although posttranslational regulatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 44 publications
5
47
0
Order By: Relevance
“…Our analysis is in line with studies of other tumor types wherein HIF2α but not HIF1α is associated with decreased tumor growth and better patient outcome (24,(38)(39)(40)(41)(42). This further underscores how tumor context determines if HIF2α acts as an oncogene (e.g., ccRCC and adult glioma) (12,26,43,44) or can actually have tumor-suppressive properties (e.g., soft tissue sarcomas, hepatocellular carcinoma, and colon cancer) (24,(38)(39)(40)(41)(42). Furthermore, in nonsmall lung cancer, HIF2α has been described both as an oncogene and a tumor suppressor (45,46).…”
Section: Discussionsupporting
confidence: 89%
“…Our analysis is in line with studies of other tumor types wherein HIF2α but not HIF1α is associated with decreased tumor growth and better patient outcome (24,(38)(39)(40)(41)(42). This further underscores how tumor context determines if HIF2α acts as an oncogene (e.g., ccRCC and adult glioma) (12,26,43,44) or can actually have tumor-suppressive properties (e.g., soft tissue sarcomas, hepatocellular carcinoma, and colon cancer) (24,(38)(39)(40)(41)(42). Furthermore, in nonsmall lung cancer, HIF2α has been described both as an oncogene and a tumor suppressor (45,46).…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, further studies have to elucidate the exact roles for the different subunits precisely vis-à-vis. Regarding colorectal cancer, one study recently described HIF-2α to prevent colorectal cancer progression [53]. Taniguchi et al further reported a beneficial effect for the HIF-2 subunit when studying the impact of PHD inhibition on radiation-induced gastrointestinal toxicity [59].…”
Section: Hif and Ibdmentioning
confidence: 99%
“…Genes regulated by EPAS1 are enriched in biological processes including signaling, cell communications, and system development because EPAS1 downstream genes are significantly enriched in hypoxia responsive gene [6]. EPAS1 gene expression is reduced in many diseases [7,8].…”
Section: Introductionmentioning
confidence: 99%